Towards a Living Standards Framework for all Aotearoa: Culture, children and wellbeing - Tim Hughes (New Zealand Government, The Treasury, 2021)
The Treasury's new Living Standards Framework (LSF) was released in a Treasury paper in October 2021.1 The 2021 version of the LSF (LSF2021) is intended to better reflect children's wellbeing and culture, including being more compatible with te ao Maori and Pacific cultures. This original proposal paper provides a richer explanation of the rationale for some of the changes in the LSF, drawing from a selective review of the enormous literatures on these topics. A draft version of this proposal paper was provided to targeted stakeholders for feedback and suggestions at the start of 2021. We then progressively worked towards a final version of the framework with those stakeholders. A such, the final version draws on both the ideas in this proposal paper and the ideas and suggestions of stakeholders. A summary of LSF2021 and the feedback provided is available in the Treasury paper. The final version of LSF2021 is similar to but simpler than this proposal. Some of the ideas in this paper were considered better treated as optional extras for advanced users of the LSF. Where there are any conflicts between this paper and the Treasury paper, the Treasury paper should be treated as the definitive statement of what the LSF is, at least until it is next updated.
Keywords: 330; Kinder; Lebensstandard; Lebensqualität; Nationalkultur; Maori; Neuseeland